Structuring a Safer Donor-Replacement Program - Liu, T. C. (Institutional Knowledge at Singapore Management University, 1998)
Replacement donors are more likely than volunteer donors to have positive or abnormal tests for transfusion-transmissible disease. In an effort to increase the donor pool, workers sought to identify a safer replacement-donor subgroup that may be acceptable for routine donations. STUDY DESIGN AND METHODS: In a retrospective review and cohort study, the replacement-donor effect was separated from the new-donor effect. The relative effect the replacement donor has on the risk of transfusion-transmissible diseases, donor retention, and frequency of returning donations was then quantified by comparison against the effect of repeat volunteer donors. RESULTS: The replacement donor had 3.1 times the risk and 0.72 times the donor retention rate and made 0.81 times as many returning donations as the repeat volunteer donor. The figures for the new-donor effect were similar. The two risks were additive, making a new replacement donor particularly hazardous. If replacement donations only from repeat replacement donors were considered, the donor risk and the number of donations per returning donor were made comparable to those for the general (combined) volunteer donor. CONCLUSION: The negative effect of the replacement donor is similar in magnitude to that of the new volunteer donor. A replacement-donation program targeting repeat replacement donors has an acceptable risk profile and may be a valuable adjunct to the collection of blood from general volunteer donors.